Pendeteksian Bit Error Dalam Transmisi Data Dengan Menerapkan Cyclic Redudancy Check - Sirait, Matias Julius Fika; Sinaga, Sony Bahagia (LPPM UNIKA Santo Thomas Medan, 2018)
The communication path that will physically connect the two technologies conceptually works together such as cables. A special feature of a channel that resembles a cable is where the bits will be forwarded in the same order along with the bits sent. Data link layers have specific functions, this function includes starting from providing interfaces for services that are good for the network layer. Communication flows often make mistakes, sometimes having limited data rates and experiencing propagation delays other than zero between when bits are sent when the bit is received. This limitation is an implication of the importance of the efficiency of data transfer. Delivery of information in the telecommunications world will often occur errors in the data to be sent. This error is caused by a disturbance at the physical level, which is a disruption of the transmission line media, such as interference with electromagnetic radiation, cross communication, lightning or noise disturbance. This interference causes the information received does not match the information sent. The Cyclical Redundancy Check method, or CRC, is a method for handling error detection, this method uses binary numbers. The CRC data detection model is sent perframe consisting of a long row of bits for each frame.